Efficacy of primed infusions with high dose ranitidine and omeprazole to maintain high intragastric pH in patients with peptic ulcer bleeding: a prospective randomised controlled study. Issue 1 (January 1997) - Labenz, J; Peitz, U; Leusing, C; Tillenburg, B; Blum, A L; Börsch, G
Abstract : BACKGROUND: In healthy subjects, continuous infusions of high dose ranitidine and omeprazole produce high intragastric pH values. AIM: To test the hypothesis that both drugs also maintain high intragastric pH values in patients with bleeding ulcers. PATIENTS AND METHODS: In two parallel studies, 20 patients with bleeding duodenal ulcers and 20 patients with bleeding gastric ulcers were randomly assigned to receive either ranitidine (0.25 mg/kg/hour after a bolus of 50 mg) or omeprazole (8 mg/hour after a bolus of 80 mg) for 24 hours. Intragastric pH was continuously recorded with a glass electrode placed 5 cm below the cardia. RESULTS: Both drugs rapidly raised the intragastric pH above 6. During the second 12 hour period, however, the percentage of time spent below a pH of 6 was 0.15% with omeprazole and 20.1% with ranitidine (p = 0.0015) in patients with duodenal ulcer; in patients with gastric ulcer it was 0.1% with omeprazole and 46.1% with ranitidine (p = 0.002). CONCLUSIONS: Primed infusions of omeprazole after a bolus produced consistently high intragastric pH values in patients with bleeding peptic ulcers, whereas primed infusions with ranitidine were less effective during the second half of a 24 hour treatment course. This loss of effectiveness may be due to tolerance.